2012
DOI: 10.3892/ol.2012.1074
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MCF-7 breast cancer cell-induced platelet aggregation using a combination of antiplatelet drugs

Abstract: Cancer metastasis is a highly coordinated and dynamic multistep process in which cancer cells interact with a variety of host cells. Morphological studies have documented the association of circulating tumor cells with host platelets. Tumor cell-induced platelet aggregation (TCIPA) contributes significantly to hematogenous metastasis; however, the molecular mechanisms involved in breast cancer TCIPA are poorly characterized. In this study, MCF-7 metastatic human breast cancer cells induced dose-dependent aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 39 publications
2
45
0
1
Order By: Relevance
“…At the site of injury, tumor cell-induced platelet activation (TCIPA) is characterized by PLT aggregation, adhesion, and a strong increase of PLT-derived pro-angiogenic factors [25]. PLTs are activated by their essential pathways, such as thromboxane (TX)-A2, glycoprotein (GP)-Ib-IX, ADP, and GPIIb/IIIa [26], leading to a dramatic increase in PLT-activation markers, such as P-selectin (CD62P) and angiogenesis mediators. Literature evidence reported that PLTs from breast cancer patients contained significantly higher levels of VEGF, angiopoietin-1, and P-selectin compared to normal controls [27]; similarly, the concentrations of VEGF and platelet-derived growth factor (PDGF) were increased in colorectal cancer patients compared to controls [28], as well as in GBM patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…At the site of injury, tumor cell-induced platelet activation (TCIPA) is characterized by PLT aggregation, adhesion, and a strong increase of PLT-derived pro-angiogenic factors [25]. PLTs are activated by their essential pathways, such as thromboxane (TX)-A2, glycoprotein (GP)-Ib-IX, ADP, and GPIIb/IIIa [26], leading to a dramatic increase in PLT-activation markers, such as P-selectin (CD62P) and angiogenesis mediators. Literature evidence reported that PLTs from breast cancer patients contained significantly higher levels of VEGF, angiopoietin-1, and P-selectin compared to normal controls [27]; similarly, the concentrations of VEGF and platelet-derived growth factor (PDGF) were increased in colorectal cancer patients compared to controls [28], as well as in GBM patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of platelet aggregation around primary tumor cells is difficult to recognize. Cancer cells were shown to have the ability to interact with platelets in vitro several decades ago (19)(20)(21)(22). Furthermore, the interaction between circulating tumor cells (CTCs) and circulating platelets is now recognized as a hallmark of the metastatic potential of cancer (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported the interaction between intrinsic subtype and tumor cell-platelet interactions. Luminal-type breast cancer cells have been reported to induce greater aggregation of platelets than other types of breast cancer cells in vitro (19,24). Moreover, in addition to facilitating tumor invasiveness, migration, tumor growth, cell survival, and angiogenesis, circulating platelets also play a crucial role in inducing EMT in malignancy (10).…”
Section: Discussionmentioning
confidence: 99%
“…A long held observation of tumor cells supporting platelet aggregation highlights the tumor cells ability to exert a thrombotic effect likely contributing to the Trousseau syndrome [32]. The aggregation mechanisms are the well characterized receptor-ligand interactions and pathways that are exquisitely described for hemostasis, such as glycoprotein (GP) Ib-IX, GPIIb/IIIa, ADP, and thromboxane [51]. …”
Section: Platelets and Cancermentioning
confidence: 99%